Ontherus sulcator Fabricius, 1775 (Coleoptera: Scarabaeidae: Scarabaeinae): Descriptions of the Third Instar and Pupa - González Vainer, Patricia (2016)
The third instar and pupa of Ontherus sulcator Fabricius are described and Illustrated. The immature stages were reared from eggs laid by adults under laboratory conditions. The morphology of the larva and pupa is analyzed based on characters at the generic level and compared with those of other related genera. Larval morphology is also compared with that of Ontherus mexicanus Harold. The larvae of O. sulcator and O. mexicanus share most of the characters proposed for the genus. These species can be distinguished by differences in chaetotaxy of the epipharynx and mandible. The pupa of O. sulcator possesses a system of pupal support projections as occurs in all known scarabeinae pupae. The number and distribution of projections are similar to those of other related genera of Dichotomiini.